Johanson-Blizzard Syndrome: Expanding the Phenotype of Exocrine Pancreatic Insufficiency - Ellery, Kate M; Erdman, Steven H (JOP. Journal of the Pancreas, 2014)
Context Johanson-Blizzard syndrome (JBS) is a rare autosomal recessive syndrome characterized by dysmorphic nasal alae, ectodermal abnormalities, exocrine pancreatic insufficiency and early growth failure. Most patients are diagnosed by clinical criteria prenatally or in early infancy. Nonsense, frame shift and splice-site mutations of the ubiquitin ligase gene (UBR1) lead to early loss of acinar cells in individuals with JBS. Case report We describe a previously asymptomatic patient with ectodermal dysplasia presenting with sudden onset exocrine pancreatic insufficiency in adolescence. The family reports an identical twin brother with similar symptoms. Conclusion This case illustrates that the phenotypic variability of pancreatic involvement in JBS may be subtle and may not manifest until the second decade of life. We suspect that this mild phenotype results from mutations in UBR1 allowing for partial function. Image. Thick yellow toe nails consistent with ectodermal dysplasia.